Public administration : an introduction - Holzer, Marc; Schwester, Richard Wilmot, 1977- (New York : Routledge, Taylor & Francis Group, 2020)
"Marc Holzer and Richard W. Schwester have written a fresh and highly engaging textbook for the introductory course in Public Administration. Their coverage is both comprehensive and cutting-edge, including not only all the basic topics (organization theory, budgeting, human resource management, etc.), but also reflecting new realities in public administration: innovations in e-government, the importance of new technology, changes in intergovernmental relations, especially the emphasis on inter-local and shared regional resources, and public performance and accountability initiatives. Public Administration has been crafted with student appeal in mind. Each of the book's chapters is generously illustrated with cartoons, quotes, and artwork--all reinforcing the book's theme that the field of public administration is rooted in the cultural and political world. Each chapter is also supported with a listing of key terms, exercises, and additional resources"--
What public administration entails -- Organizational theory and management -- Politics and public administration -- Intergovernmental relations -- Ethics and public administration -- Managing human resources -- Public decision making -- Public sector leadership -- Public budget -- Public performance -- Program and policy assessment -- Existing data, big data and analyzing data -- Technology and public administration -- The future of public administration.
Includes bibliographical references and index.
Keywords: Public administration; Public administration -- Decision making; Policy sciences; Policy sciences; Public administration; Public administration -- Decision making